FAKTOR PEJAMU DAN LINGKUNGAN SOSIAL BUDAYA MEMPENGARUHI KEJADIAN INFEKSI MENULAR SEKSUAL (IMS) PADA IBU RUMAH TANGGA (Studi Kasus di Wilayah Kerja Puskesmas Bandarharjo Semarang) - Aysanti Yuliana Paulus (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2018)
Background : STIs are big problem in society’s health, especially as a consequences of sexual health and reproduction towards women, children and the poor. Women suffering from some STIs, such as gonorrhea and chlamydia can cause pelvic inflammatoion disease, ectopic pregnancy, and infertility, whereas HSV-2 infections can treble a risk of transmitted HIV or more. This study aim to prove the factors influencing with STIs towards housewives. Method: This study resulted mix method where quantitative was as the main approach with case-control design and qualitative, supportted by qualitative method using indepth interview. The target population was all housewives using clinic of STI at Puskesmas Bandarharjo, with the sample of 88 people consisting of 44 cases and 44 controls by using consecutive sampling technique. The writter gradually analysed the data, from univariate and bivariate analysis by using chi-square, followed by multivariate analysis by using multiple logistic regression. Result: The results show the factors influencing with STIs towards housewives are history of previous STI (p = 0.001; OR = 19.5; CI95% = 3.4 to 112.1), who have ever experienced domestic violence (p = 0.042; OR = 4.4; CI95%= 1.1 to 18.2), and have permissive culture (p = 0.009; OR = 7.8; CI95%= 1.7 to 36.1) with probability to be infection is 98.06%.Conclusion: The result of this study can beconcluded that there is a relationship between history of previous STI, who have ever experienced domestic violence, and have permissive culture with STIs at Puskesmas Bandarharjo.Key Words: STIs, housewife, factor influecing.